Fibrous histiocytoma of the lung. - Viguera, J L (1976)
A case of asymptomatic fibrous histiocytoma of the lung is described in a 14-year-old girl. A left thoracotomy was performed followed by partial resection of the lingula. Postoperative progress was uneventful.